Attention and multisensory integration of emotions in schizophrenia - Zvyagintsev, Mikhail; Parisi, Carmen; Chechko, Natalia; Nikolaev, Andrey R.; Mathiak, Klaus (Frontiers in Human Neuroscience, 2013)
The impairment of multisensory integration in schizophrenia is often explained by deficits of attentional selection. Emotion perception, however, does not always depend on attention because affective stimuli can capture attention automatically. In our study, we specify the role of attention in the multisensory perception of emotional stimuli in schizophrenia. We evaluated attention by interference between conflicting auditory and visual information in two multisensory paradigms in patients with schizophrenia and healthy participants. In the first paradigm, interference occurred between physical features of the dynamic auditory and visual stimuli. In the second paradigm, interference occurred between the emotional content of the auditory and visual stimuli, namely fearful and sad emotions. In patients with schizophrenia, the interference effect was observed in both paradigms. In contrast, in healthy participants, the interference occurred in the emotional paradigm only. These findings indicate that the information leakage between different modalities in patients with schizophrenia occurs at the perceptual level, which is intact in healthy participants. However, healthy participants can have problems with the separation of fearful and sad emotions similar to those of patients with schizophrenia.